Legitimacy of the Build, Operate, and Transfer (BOT) Agreement between the Indonesian Navy Marine Corps and PT Karya Tumbuh Bersama Indo - Yoserizal, Yoserizal; Setyowati, Retno Kus; Sulasih, Rr. Endang Sri (Program Doktor Ilmu Hukum, Universitas Krisnadwipayana, 2024)
This study examines the validity of the Build, Operate, and Transfer (BOT) Agreement between the Indonesian Marine Corps and PT Karya Tumbuh Bersama Indo regarding the construction and management of Plaza Cilandak, as well as the impact of the implementation of the Minister of Finance Regulation No. 54/PMK.06/2015 concerning the management of State-Owned Assets (BMN) on the existing agreement. Using a normative legal approach, this research analyzes the agreement’s compliance with the essential elements of validity as regulated in the Civil Code and the implications of the new regulations on the already signed contract. The findings indicate that the BOT agreement is legally valid, but the implementation of the new regulation requires renegotiation between the private sector and the government. This study also highlights the importance of applying the Pacta Sunt Servanda principle to maintain legal certainty in the BOT agreement, and the necessity of dialogue between the private sector and the government to avoid disputes and ensure the project’s sustainability.